Alternatives to freedom: expressions of empowerment in the Malay female body - Goon, Jeannette (2022)
Discussions on sex and sexuality in Malaysia have increased in the last decade. The rhetoric used in urban, liberal, and typically English-speaking spheres implies that conversations about sex are taboo and stigmatised, as well as suggests that there is a need for women to reclaim their bodies. However, this contradicts what is being observed in the supposedly conservative, Malay-language spheres. Not only is sexual (and at times, pornographic) content ubiquitous, but it is also not always stigmatised. At the same time, these do not position women as subordinate or passive bodies. This dissertation explores that contradiction, with a focus on the Malay woman’s body as it manifests in the three registers of Lacanian psychoanalysis – the Imaginary, The Symbolic, and the Real. It analyses women-produced live-streamed pornography on the Internet, pornographic marketing of traditional penis medications on social media, and confessions of supernatural disturbances to show that: 1) Malay women continue to sustain their historically established cultural power and 2) that despite restrictions on their bodies, Malay/sian women have other strategies to assert their authority. Ultimately, what this dissertation argues is that concepts of gender that are hegemonic in Western society are not always applicable in the Malay context. Thus, there is a need for other theories beyond feminism to examine gender and how it relates to power in Malaysia, as well as Southeast Asia.